2017
DOI: 10.1175/jcli-d-16-0712.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Low-Frequency Internal Climate Variability in CMIP5 Models and Observations

Abstract: Low-frequency internal climate variability (ICV) plays an important role in modulating global surface temperature, regional climate, and climate extremes. However, it has not been completely characterized in the instrumental record and in the Coupled Model Intercomparison Project phase 5 (CMIP5) model ensemble. In this study, the surface temperature ICV of the North Pacific (NP), North Atlantic (NA), and Northern Hemisphere (NH) in the instrumental record and historical CMIP5 all-forcing simulations is isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 66 publications
(107 reference statements)
3
51
0
Order By: Relevance
“…The reanalysis/CMIP5 differences in jet strength variability are most prominent for periods of approximately 70 years (Figure ), which is consistent with a link between multidecadal variability in jet strength and AMV that was identified previously by Woollings et al (, who found a correlation of −0.48 between AMV and multidecadal jet strength variability using a similar jet strength metric). Studies show that the observed AMV is stronger than that in most CMIP5 models (Cheung et al, ; Zhang & Wang, ). The comparatively prominent observed low‐frequency strength variability compared to CMIP5 is consistent with previous work suggesting a too weak feedback between AMV and atmospheric variability (Kim et al, ; Peings et al, ; Wang et al, ).…”
Section: Discussionmentioning
confidence: 92%
“…The reanalysis/CMIP5 differences in jet strength variability are most prominent for periods of approximately 70 years (Figure ), which is consistent with a link between multidecadal variability in jet strength and AMV that was identified previously by Woollings et al (, who found a correlation of −0.48 between AMV and multidecadal jet strength variability using a similar jet strength metric). Studies show that the observed AMV is stronger than that in most CMIP5 models (Cheung et al, ; Zhang & Wang, ). The comparatively prominent observed low‐frequency strength variability compared to CMIP5 is consistent with previous work suggesting a too weak feedback between AMV and atmospheric variability (Kim et al, ; Peings et al, ; Wang et al, ).…”
Section: Discussionmentioning
confidence: 92%
“…Our results are also broadly consistent with recent analyses of Cheung et al [], who documented substantial mismatches between their estimated internal components of the observed and CMIP5‐simulated AMO, PMO, and NMO variability. However, these authors used subtraction of the scaled CMIP5 MMEM signal to deduce the internal variability in historical simulations of individual CMIP5 models.…”
Section: Discussionmentioning
confidence: 99%
“…Our present methodology alleviates these problems and provides consistent estimates of the CMIP5‐simulated internal variability in the historical and preindustrial control runs. In particular, we find that Cheung et al [] underestimate the true differences between the observed (semiempirical) internal variability and the internal variability in historical CMIP5 simulations.…”
Section: Discussionmentioning
confidence: 99%
“…The AMV imprint on global and Northern Hemisphere mean surface temperature has also been identified in many studies with different statistical analysis methods applied to both observations and modeling results (Barcikowska et al, ; Chen et al, ; Chen & Tung, ; Cheung et al, ; Chylek, Klett, et al, ; Chylek et al, ; DelSole et al, ; Kravtsov et al, ; Kravtsov & Spannagle, ; Steinman et al, ; Stolpe et al, ; Tung & Zhou, ; Z. Wu, Huang, et al, ; Wyatt et al, ; Zhou & Tung, ). These statistical studies are consistent with the above‐mentioned AGCM/hybrid CGCM experiments (Semenov et al, ; Zhang et al, ), illustrating that the enhanced surface heat flux released from the ocean to the atmosphere during a positive AMV and AMOC phase leads to the hemispheric‐scale anomalous surface warming and vice versa.…”
Section: Climate Impacts Of Multidecadal Amoc Variability and Amvmentioning
confidence: 99%